2009
DOI: 10.1152/ajplung.00148.2009
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ ligands induce heme oxygenase-1 in lung fibroblasts by a PPARγ-independent, glutathione-dependent mechanism

Abstract: Oxidative stress plays an important role in the pathogenesis of pulmonary fibrosis. Heme oxygenase-1 (HO-1) is a key antioxidant enzyme, and overexpression of HO-1 significantly decreases lung inflammation and fibrosis in animal models. Peroxisome proliferator-activated receptor-gamma (PPARgamma) is a transcription factor that regulates adipogenesis, insulin sensitization, and inflammation. We report here that the PPARgamma ligands 15d-PGJ2 and 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO), which have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
(93 reference statements)
1
41
0
1
Order By: Relevance
“…We have previously shown that CDDO potently up-regulates expression of oxidative stressresponse proteins in a glutathionedependent manner and that NAC inhibits this up-regulation (29,41). Here, we show that NAC blocks up-regulation of HO-1 but does not inhibit the ability of CDDO to reduce TG2 expression ( Figure 5C).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We have previously shown that CDDO potently up-regulates expression of oxidative stressresponse proteins in a glutathionedependent manner and that NAC inhibits this up-regulation (29,41). Here, we show that NAC blocks up-regulation of HO-1 but does not inhibit the ability of CDDO to reduce TG2 expression ( Figure 5C).…”
Section: Discussionsupporting
confidence: 54%
“…Cells were incubated with the dominantnegative (DN) PPARg lentiviral vector (29) and polybrene in serum-free media for 2 hours. Growth media was then added, and transfection was assessed by green fluorescence protein (GFP) fluorescence 48 hours later.…”
Section: Pparg Lentivirusmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to see a beneficial effect of rosiglitazone on the sFlt-1/VEGF balance (as a consequence of alterations in placental HO-1 expression) it may be necessary to implement treatment at the point of surgical intervention (ie, RUPP surgery on GD14) as per cobalt (III) protoporphyrin IX chloride treatment. However, although rosiglitazone has been shown to upregulate HO-1 expression in both vascular smooth muscle and endothelial cells 10 it failed to do so in lung fibroblasts, 38 which may suggest a cell-specific effect that does not extend to the most abundant placental cell type, the trophoblast. Thus, in the present study, the beneficial effects of rosiglitazone, in terms of both vascular function and blood pressure, may simply be mediated by direct modulation of endothelial HO-1 activity, because these effects were abrogated by the HO-1 activity inhibitor SnPP.…”
Section: Discussionmentioning
confidence: 99%